Infantile Nosocomial Myiasis in Iran - Naseh Maleki-Ravasan; Mansoureh Shayeghi; Babak Najibi; MohammadAli Oshaghi (Tehran University of Medical Sciences, 2015)
Myiasis, the invasion of live human tissue by larva of Diptera, is reported in the nasal cavity of a 5.5- year-old Iranian girl. She was referred from Golestan Province to the Shaheed Rajaei Heart Center in Tehran. In the 41th day after admission, a live parasite was found in her nasal secretions suction identified presumably as a second instar larvae of a facultative myiasis, Woholfartia nuba (Diptera: Sarcophagidae), on the basis of mtDNA-COI and morphological characteristics. Since presence of the larva was recorded after hospitalization, by definition, this infestation is considered a nosocomial myiasis.